2022
DOI: 10.1177/10760296221091770
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Anti-PF4 Antibody Isotypes and Endogenous Glycosaminoglycans and their Relationship with Inflammatory Biomarkers in Pulmonary Embolism Patients

Abstract: Introduction Previous studies have shown that inflammation may contribute to the interplay of endogenous glycosaminoglycans (GAGs) and anti-PF4 antibodies. In this study, we quantified the levels of anti-PF4 antibody isotypes and endogenous GAGs together with inflammatory biomarkers in pulmonary embolism (PE) patients to determine whether there is a relationship in between. Identification of this relationship may provide insight to the complex pathophysiology of PE and HIT and may also be useful for developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…75 In a recent analysis performed by our group, has shown that the levels of endogenous GAGs were elevated in PE patients, and this was also associated with PE severity and mortality. 76,77 In the current study, our findings are similar to a previous report showing elevated levels of endogenous GAGs in PE patient plasma compared to NHP, both before and after heparinase-I degradation which is likely the result of endothelial damage and glycocalyx degradation leading to PE development in these patients. The high percentage of decrease in endogenous GAG levels after heparinase-I administration might be the result of heparin contamination of plasma samples in which therapeutic heparin is the main treatment option in this patient group.…”
Section: Discussionsupporting
confidence: 91%
“…75 In a recent analysis performed by our group, has shown that the levels of endogenous GAGs were elevated in PE patients, and this was also associated with PE severity and mortality. 76,77 In the current study, our findings are similar to a previous report showing elevated levels of endogenous GAGs in PE patient plasma compared to NHP, both before and after heparinase-I degradation which is likely the result of endothelial damage and glycocalyx degradation leading to PE development in these patients. The high percentage of decrease in endogenous GAG levels after heparinase-I administration might be the result of heparin contamination of plasma samples in which therapeutic heparin is the main treatment option in this patient group.…”
Section: Discussionsupporting
confidence: 91%
“…Though their relevance has not yet been assessed in large scale studies it is likely that these may also serve as a key method of quantifying endothelial dysfunction. 30 Together with vWF, we considered these to be markers of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%